2011
DOI: 10.1007/s12576-011-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfacalcidol on circulating cytokines and growth factors in rat skeletal muscle

Abstract: Supra-physiological levels of vitamin D induce skeletal muscle atrophy, which may be particularly detrimental in already sarcopaenic elderly. Neither the cause nor whether the atrophy is fibre type specific are known. To obtain supraphysiological levels of circulating vitamin D (1,25(OH) 2 D 3 ) 27.5-month-old female Fischer 344 9 Brown Norway F1 rats were orally treated for 6 weeks with vehicle or the vitamin D analogue alfacalcidol. Alfacalcidol treatment induced a 22% decrease in body mass and 17% muscle at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Belenchia et al [ 33 ] also observed loss of lean mass in mice due to dietary vitamin D deficiency (serum 25‑OH vitamin D < 10 ng/ml) of approximately 40 weeks in female mice initiated at 8 weeks of age. We suspect our study was underpowered to identify such histological differences; however, the possibility that vitamin D insufficient mice exhibit smaller fast twitch fiber CSA is supported by our finding that vitamin D insufficient mice also exhibit greater expression of atrogin-1, for which this and other atrophy associated proteins have previously been linked to vitamin D signaling [ 27 , 34 , 35 ]. Thus these data support the notion that long-term vitamin D insufficiency may contribute to the progression of sarcopenia.…”
Section: Discussionmentioning
confidence: 90%
“…Belenchia et al [ 33 ] also observed loss of lean mass in mice due to dietary vitamin D deficiency (serum 25‑OH vitamin D < 10 ng/ml) of approximately 40 weeks in female mice initiated at 8 weeks of age. We suspect our study was underpowered to identify such histological differences; however, the possibility that vitamin D insufficient mice exhibit smaller fast twitch fiber CSA is supported by our finding that vitamin D insufficient mice also exhibit greater expression of atrogin-1, for which this and other atrophy associated proteins have previously been linked to vitamin D signaling [ 27 , 34 , 35 ]. Thus these data support the notion that long-term vitamin D insufficiency may contribute to the progression of sarcopenia.…”
Section: Discussionmentioning
confidence: 90%
“…Tubes were heated at 25°C for 5 min, followed by 42°C for 20 min. Finally, to stop the reaction, the tubes were heated at 85°C for 5 min and stored at −80°C until used in the quantitative PCR reaction (method described previously) [19]. Expression levels of mRNA were assessed for insulin-like growth factor 1Ea (IGF-1Ea), myostatin, α -skeletal actin, muscle ring finger 1 (MuRF-1) and muscle atrophy F-box (MAFbx; also known as artogin 1) (see Table 1 for primer sequences).…”
Section: Methodsmentioning
confidence: 99%
“…Tubes were heated at 25-C for 5 min, followed by 42-C for 20 min. Finally, to stop the reaction, the tubes were heated at 85-C for 5 min and stored at j80-C until used in the quantitative polymerase chain reaction (PCR) (method described previously) (27). Expression levels of mRNA were assessed for SDH, PGC-1>, receptor-interacting protein 140 (RIP140), and BCL2/adenovirus E1B 19 kDa-interacting protein 3 (BNIP3) (see Table 1 for primer sequences).…”
Section: Methodsmentioning
confidence: 99%